2020
DOI: 10.15578/ifrj.26.1.2020.51-60
|View full text |Cite
|
Sign up to set email alerts
|

STOCK STATUS OF BLUE SWIMMING CRAB (Portunus pelagicus) IN TANAH LAUT, SOUTH KALIMANTAN, AND ITS ADJACENT WATERS

Abstract: A study on the stock status of blue swimming crab (Portunus pelagicus Linnaeus, 1758) was conducted in Tanah Laut, South Kalimantan waters, based on data collected in March to November 2017. The results showed that the growth pattern of blue swimming crab in Tanah Laut waters was negatively allometric and the sex ratio of males to females was 1.0 : 1.7. The chi-square test indicated that the total males and total females of the blue swimming crab was significantly different. It means that there was an imbalanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
6
0
3
Order By: Relevance
“…The BSC's SPR in Spermonde Islands is considerably low compared to other fishing grounds in Indonesia. For example, BSC's SPR in Tanah Laut was reported to be (Suman et al, 2020), Kasiputeh 13% (Prince, 2014), and Java Sea 15% (Ernawati et al, 2017). However, it is slightly higher when compared with the SPR in Belitung Island which was only 5% (Ernawati et al, 2015).…”
Section: Spawning Potential Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The BSC's SPR in Spermonde Islands is considerably low compared to other fishing grounds in Indonesia. For example, BSC's SPR in Tanah Laut was reported to be (Suman et al, 2020), Kasiputeh 13% (Prince, 2014), and Java Sea 15% (Ernawati et al, 2017). However, it is slightly higher when compared with the SPR in Belitung Island which was only 5% (Ernawati et al, 2015).…”
Section: Spawning Potential Ratiomentioning
confidence: 99%
“…Analysis of carapace width will provide information on Bartalanffy growth parameters (K, L∞, t0) and size at first captured. Gonad Maturity Stage (GMS) analysis will produce information on size at first maturity (Lm 50 ) (Hordyk et al, 2015;Wujdi & Wudianto, 2015;Permatahati et al, 2020;Suman et al, 2020). Previous study has been done by researchers concerning input parameters required for BSC's SPR study in Spermonde Islands using different analysis (Table 1).…”
Section: Data Analysis Spawning Potential Ratiomentioning
confidence: 99%
“…Blue swimming crab (BSC) (Portunus pelagicus Linnaeus, 1758) is a fisheries resource with crucial economic value [1] and a high export market [2], which is exported mainly to the US [3], Singapore [4], Japan [5], and Netherlands [6]. The BSC export volume in 2017-2019 was 27.792 tonnes with an export value of US$ 472 million [7].…”
Section: Introductionmentioning
confidence: 99%
“…This species is widely dispersed in Indonesia, spreading from the western coast of Sumatera to the northern coast of Java [4], the southern and eastern coasts of Kalimantan, the southern part of Sulawesi, and the western area of Papua [8]. So far, to meet market demand, fishermen still rely on catches directly from nature [6] using traps and gill nets [9]. There had been no aquaculture activity as it was still in the research process and the best aquaculture technique has not been found [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation